Reševanje problemov zlaganja z uporabo simuliranega izničenja in genetskih algoritmov - Gomez, Alberto (Strojniški vestnik, 2005)
The aim of this paper is to present two algorithms that are designed to optimise the cutting process of an L-type guillotine and to minimise the number of sheets used to manufacture a number of rectangular pieces. Two algorithms are proposed, one based on genetic algorithms and the other on simulated annealing. They are compared with the help of a bank of examples. Both algorithms provide very good results, although each of them has its peculiarities, which are described in this paper.
Keywords: algoritmi genetski; zlaganje; postopki rezanja; optimiranje postopkov; genetski algoritmi; rezanje; optimiranje